The effect of PFAS exposure on glucolipid metabolism in children and adolescents: a meta-analysis - Zheng, Qingqing; Yan, Wu; Gao, Shenghu; Li, Xiaonan (Frontiers in Endocrinology, 2024)
Background: Previous studies showed that per- and polyfluoroalkyl substances (PFASs), which are widely found in the environment, are capable of disrupting endocrine homeostasis when they enter the human body. This meta-analysis aims to evaluate the current human epidemiological evidence on the relationship between PFASs exposure and glucolipid metabolism in childhood and adolescence. Methods: By searching PubMed, Web of Science, Embase, and Cochrane Library databases, we identified population-based epidemiological studies related to PFASs and glucolipid metabolism indexes, which were published before December 30, 2022. The heterogeneity of the included literature was assessed by the I-square (I2) test and statistics Q. Random-effects and fixed-effects models were used to combine effect size. Subgroup analysis based on the age and gender of study participants was performed. Sensitivity analysis was used to evaluate the robustness and reliability of the combined results. The Egger's and Begg's tests were used to analyze publication bias. Result: A total of 12 studies were included in the analysis. There was a positive association between PFASs and TC (β=1.110, 95% CI: 0.601, 1.610) and LDL (β=1.900, 95% CI: 1.030, 2.770)， a negative association between PFASs and HOMA-IR in children and adolescents (β=-0.130, 95% CI: -0. 200, -0.059). PFOS was significant positive associated with TC (β=8.22, 95% CI: 3.93, 12.51), LDL (β= (12.04, 95% CI: 5.08, 18.99), and HOMA-IR (β=-0.165, 95% CI: -0.292, -0.038). Subgroup analysis showed that exposure to PFASs in the adolescent group was positively associated with TC and LDL, the relationship was more strongly in females. Conclusion: PFASs exposure is associated with glucolipid metabolism in children and adolescents. Among them, PFOS may play an important role. Recognition of environmental PFAS exposure is critical for stabilizing the glycolipid metabolism relationship for the growth and development of children and adolescents.